Effectiveness of Stabilization of Preterm Infants With Intact Umbilical Cord Using a Purpose-Built Resuscitation Table—Study Protocol for a Randomized Controlled Trial - Knol, Ronny; Brouwer, Emma; Klumper, Frans J. C. M.; van den Akker, Thomas; DeKoninck, Philip; Hutten, G. J.; Lopriore, Enrico; van Kaam, Anton H.; Polglase, Graeme R.; Reiss, Irwin K. M.; Hooper, Stuart B.; te Pas, Arjan B. (Frontiers in Pediatrics, 2019)
Background: Most preterm infants fail to aerate their immature lungs at birth and need respiratory support for cardiopulmonary stabilization. Cord clamping before lung aeration compromises cardiovascular function. Delaying cord clamping until the lung has aerated may be beneficial for preterm infants by optimizing hemodynamic transition and placental transfusion. A new purpose-built resuscitation table (the Concord) has been designed making it possible to keep the cord intact after preterm birth until the lung is aerated and the infant is respiratory stable and breathing (Physiological-Based Cord Clamping (PBCC)). The aim of this study is to test the hypothesis whether stabilizing preterm infants by PBCC is at least as effective as the standard approach using time-based Delayed Cord Clamping (DCC). Study design: This is a randomized controlled non-inferiority study including 64 preterm infants born at less than 32 weeks of gestation. Infants will be randomized to either the PBCC approach or standard DCC. In case of PBCC, infants will be stabilized with an intact umbilical cord and the cord will only be clamped when the infant is considered respiratory stable, defined as the establishment of regular spontaneous breathing, a heart rate ≥ 100 bpm and oxygen saturation above 90% while using inspired fraction of oxygen (FiO2) < 0.40. The Concord will be used, which allows giving respiratory support on an intact umbilical cord. In the DCC group infants are clamped first before they are transferred to the standard resuscitation table for further treatment and stabilization. Cord clamping is time-based and delayed at 30-60 seconds. The primary outcome will be the time to respiratory stability of the infant, starting from birth. Secondary outcomes will include details of stabilization, important clinical outcomes of prematurity and maternal safety outcomes. Discussion: We expect that PBCC using the Concord may reduce major morbidities and mortality in preterm infants. The current study protocol will assess the effectivity of stabilization. Once effectivity of stabilization is confirmed, we will start a large multicenter randomized clinical trial to investigate whether PBCC reduces mortality and morbidity in preterm infants compared to the standard approach.